Expanding the phenotypic and biochemical spectrum of NDUFAF3-related mitochondrial disease - Ven, Amelie T. van der; Cabrera-Orefice, Alfredo; Wente, Isabell; Feichtinger, René G.; Tsiakas, Konstantinos; Weiss, Deike; Bierhals, Tatjana; Scholle, Leila; Prokisch, Holger; Kopajtich, Robert; Santer, René; Mayr, Johannes A.; et al. (Molecular genetics and metabolism, 2023)
Recessive variants in NDUFAF3 are a known cause of complex I (CI)-related mitochondrial disorders (MDs). The seven patients reported to date exhibited severe neurologic symptoms and lactic acidosis, followed by a fatal course and death during infancy in most cases. We present a 10-year-old patient with a neurodevelopmental disorder, progressive exercise intolerance, dystonia, basal ganglia abnormalities, and elevated lactate concentration in blood. Trio-exome sequencing revealed compound-heterozygosity for a pathogenic splice-site and a likely pathogenic missense variant in NDUFAF3. Spectrophotometric analysis of fibroblast-derived mitochondria demonstrated a relatively mild reduction of CI activity. Complexome analyses revealed severely reduced NDUFAF3 as well as CI in patient fibroblasts. Accumulation of early sub-assemblies of the membrane arm of CI associated with mitochondrial complex I intermediate assembly (MCIA) complex was observed. The most striking additional findings were both the unusual occurrence of free monomeric CI holding MCIA and other assembly factors. Here we discuss our patient in context of genotype, phenotype and metabolite data from previously reported NDUFAF3 cases. With the atypical presentation of our patient, we provide further insight into the phenotypic spectrum of NDUFAF3-related MDs. Complexome analysis in our patient confirms the previously defined role of NDUFAF3 within CI biogenesis, yet adds new aspects regarding the correct timing of both the association of soluble and membrane arm modules and CI-maturation as well as respiratory supercomplex formation.